How physical exercise impacts academic burnout in college students: The mediating effects of self-efficacy and resilience - Chen, Kai; Liu, Feiyang; Mou, Liu; Zhao, Peiting; Guo, Liya (Frontiers in Psychology, 2022)
Background and Aims: Academic burnout is harmful to college students, their institutions of learning, and society at large. While research has shown that physical exercise may be associated with reduced academic burnout, the underlying mechanisms require further exploration. This study explored the relationship between physical exercise and academic burnout in a sample of college students, with a focus on the serial mediating roles of self-efficacy and resilience. Methods: This study adopted a cross-sectional survey approach among a sample of college students in China. We recruited 1,270 total participants (476 men and 794 women), all of whom completed questionnaires containing the Physical Activity Rating Scale (PARS-3), Academic Burnout Scale for College Students, 10-item General Self-Efficacy Scale, and 25-item Connor-Davidson Resilience Scale (CD-RISC). We then subjected the collected data to a series of statistical analyses. Results and Conclusion: Physical exercise was significantly and negatively associated with academic burnout and its three subfactors (i.e., emotional exhaustion, improper behavior, and low personal achievement). Participants in the high physical exercise group showed lower levels of academic burnout than those in the moderate and low physical exercise groups. Finally, our serial mediation model showed that physical exercise had a significant direct effect on academic burnout (β = -0.2652, 95% CI = [-0.1421,-0.0791]) in addition to significant indirect effects on academic burnout via self-efficacy and resilience (β = -0.0802, 95% CI = [-0.1088,-0.0527]). These findings suggest that physical exercise is an important interventional target when aiming to reduce academic burnout.